Aztreonam is a novel chemical inducer that promotes Agrobacteium transformation and lateral root development in soybean - M. Waqar Khan; Wenqi Yang; Ke Yu; Xuebin Zhang (Frontiers in Microbiology, 2023)
Agrobacterium-mediated soybean transformation is the simplest method of gene transfer. However, the low transformation due to the intractable nature of soybean genotypes hinders this process. The use of biochemicals (acetosyringone, cinnamic acid, flavonoids, etc.) plays an important role in increasing soybean transformation. These biochemicals induce chemotaxis and virulence gene activation during the infection process. Here we identified a biochemical, aztreonam (a monobactam), for high agrobacterium-mediated transformation in soybean. The soybean explants from three genotypes were inoculated with A. tumefaciens (GV3101) harboring the pMDC32 vector containing hpt or the GmUbi-35S-GUS vector containing the GUS gene during two separate events. High transient GUS expression was obtained during cotyledon explant culture on MS media supplemented with 2.5 mg/L aztreonam. The aztreonam-treated explants showed high efficiency in transient and stable transformation as compared to the untreated control. The transformation of aztreonam-treated explants during seed imbibition resulted in an average of 21.1% as compared to 13.2% in control by using the pMDC32 vector and 28.5 and 20.7% while using the GUS gene cassette, respectively. Based on these findings, the metabolic analysis of the explant after aztreonam treatment was assessed. The high accumulation of flavonoids was identified during an untargeted metabolic analysis. The quantification results showed a significantly high accumulation of the four compounds, i.e., genistein, apigenin, naringenin, and genistin, in cotyledon explants after 18 hours of aztreonam treatment. Alongside this, aztreonam also had some surprising effects on root elongation and lateral root formation when compared to indole-3-butyric acid (IBA). Our findings were limited to soybeans. However, the discovery of aztreonam and its effect on triggering flavonoids could lead to the potential role of aztreonam in the agrobacterium-mediated transformation of different crops.